2019
DOI: 10.3390/rs11070842
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Wetland Inventory using Google Earth Engine: The First Map and Preliminary Results

Abstract: Although wetlands provide valuable services to humans and the environment and cover a large portion of Canada, there is currently no Canada-wide wetland inventory based on the specifications defined by the Canadian Wetland Classification System (CWCS). The most practical approach for creating the Canadian Wetland Inventory (CWI) is to develop a remote sensing method feasible for large areas with the potential to be updated within certain time intervals to monitor dynamic wetland landscapes. Thus, this study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
100
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(102 citation statements)
references
References 39 publications
0
100
1
1
Order By: Relevance
“…All of these demonstrated that deep learning results outperform other machine learning methods such as random forest. Non-neural network methods, such as the work in Amani et al [83], reported a 71% wetland class accuracy across all of Canada. Another study by Mahdianpari et al [34] achieved 88% wetland class accuracy using an object-based random forest algorithm across Newfoundland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these demonstrated that deep learning results outperform other machine learning methods such as random forest. Non-neural network methods, such as the work in Amani et al [83], reported a 71% wetland class accuracy across all of Canada. Another study by Mahdianpari et al [34] achieved 88% wetland class accuracy using an object-based random forest algorithm across Newfoundland.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies are now using a fusion of remote sensing data from SAR, optical, and DEM products [6,7,34,39,49]. The easiest way to access provincial/national-scale data appears to be through Google Earth Engine; thus, many studies use Sentinel-1, Sentinel-2, Landsat, ALOS, or SRTM data [6,7,34,83]. Finally, many machine learning methods have been tested, but it appears that convolutional neural network frameworks produce better, more accurate wetland/landcover classifications [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…We suspect omission of these local within‐wetland covariates is why our models for sora and Virginia rail performed so poorly, as these species respond strongly to immediate wetland vegetation structure and food availability, and less to wetland and landscape‐scale covariates (Fairbairn and Dinsmore 2001, Naugle et al 2001, Baschuk et al 2012, Tozer 2016, Saunders et al 2019). Developing these covariates and associated improved models and predictive maps are important areas for future research, some of which could potentially be achieved through automated remote sensing (Feyisa et al 2014, Bourgeau‐Chavez et al 2015, Amani et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The GEE greatly improves the processing efficiency when using substantial amounts of remote sensing data. In recent years, the GEE was used in land cover mapping [49][50][51][52][53][54][55][56][57][58], agricultural applications [59][60][61][62][63], disaster management, and earth sciences studies [64][65][66]. This remote sensing data processing cloud platform makes the rapid processing of Sentinel-2 images covering large areas possible.…”
mentioning
confidence: 99%